Photodiaries of manomin on the Upper Winnipeg River ... - Bradford, Andrea; Luby, Brittany; Niisaachewan Anishinaabe Nation (Borealis, 2022)
This image collection or photodiary was intended to document the extent and density of manomin growth at each visible life stage at sites selected by Elders from Niisaachewan Anishinaabe Nation. It was also intended to monitor the extent and density of invasive hybrid cattail, a species that competes with the manomin for territory. Manomin is commonly and inaccurately known as "wild rice" in English. Its Latin name is Zizania palustris. ...